2023
DOI: 10.3324/haematol.2022.282177
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory molecule TIGIT is expressed by chronic lymphocytic leukemia cells and contributes to anergy

Abstract: T-cell immunoreceptor with Ig and ITIM domains (TIGIT) is an inhibitory checkpoint receptor that negatively regulates T cell responses. CD226 competes with TIGIT for binding to the CD155 ligand, delivering a positive signal to the T cell. Here we studied expression of TIGIT and CD226 in a cohort of 115 chronic lymphocytic leukemia (CLL) patients and report expression of TIGIT and CD226 by leukemic cells. By devising a TIGIT/CD226 ratio, we showed that CLL cells favoring TIGIT over CD226 are typical of a more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…First, in patients with chronic lymphocytic leukemia (CLL), AML, or adult acute lymphoblastic leukemia (ALL), TIGIT is commonly upregulated on CD4 + T cells, CD8 + T cells, Foxp3 + γδ T cells, or NK cells compared with healthy individuals [64][65][66][67][68][69][70]. Notably, TIGIT leads to CLL anergy by downregulating B cell receptor signaling [71]. It correlates with T cell exhaustion, NK cell dysfunction, unfavorable responses after chemotherapy, and leukemia relapse after allogeneic hematopoietic stem cell transplantation in AML patients [66,67,69,70].…”
Section: Tigit In Solid Tumors and Hematological Malignanciesmentioning
confidence: 99%
“…First, in patients with chronic lymphocytic leukemia (CLL), AML, or adult acute lymphoblastic leukemia (ALL), TIGIT is commonly upregulated on CD4 + T cells, CD8 + T cells, Foxp3 + γδ T cells, or NK cells compared with healthy individuals [64][65][66][67][68][69][70]. Notably, TIGIT leads to CLL anergy by downregulating B cell receptor signaling [71]. It correlates with T cell exhaustion, NK cell dysfunction, unfavorable responses after chemotherapy, and leukemia relapse after allogeneic hematopoietic stem cell transplantation in AML patients [66,67,69,70].…”
Section: Tigit In Solid Tumors and Hematological Malignanciesmentioning
confidence: 99%
“… 8 , 13 Peripheral blood analysis of CLL patients showed that TIGIT-positive CD4 T cells were increased over healthy controls, especially in more advanced disease stages. 14 Arruga et al 29 show that TIGIT is more highly expressed on CLL/SLL cells in the peripheral blood when compared with CD19-positive cells from healthy donors. Our results in tissue biopsies of CLL/SLL show frequent TIGIT expression in the TME, but not on lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, high TIGIT expression in lymph node biopsies of CLL patients was associated with a lower proliferation rate of CLL cells, whereas CD226 expression was linked to greater proliferation, which is in line with the concept that TIGIT induces anergy of CLL cells. In support of this, Arruga et al show that a high TIGIT to CD226 ratio was predictive for good prognosis in CLL, 1 whereas TIGIT expression was low or absent and CD226 expression was high in Richter’s syndrome, an aggressive transformation of CLL that is driven by highly proliferative B cells. 11 Altogether, this suggests that TIGIT in CLL cells is linked to anergy and a limited proliferation rate ( Figure 1C ).…”
mentioning
confidence: 91%
“…In this issue of Haematologica , Arruga and colleagues add to the list of these genes another interesting molecule which is TIGIT: T-cell immunoreceptor with Ig and ITIM domains. 1 TIGIT is an inhibitory checkpoint receptor that is up-regulated by T cells and natural killer cells upon antigen recognition and limits their response. Like PD-1, it is associated with dysfunctional or exhausted T cells in cancer and is, therefore, currently being tested as a novel immunotherapy target in several clinical trials where dual blockade of PD-(L)1 and TIGIT shows promising early results in cancer patients.…”
mentioning
confidence: 99%